Treatment of Gangrene Wounds with Hydrocolloid Dressing Methods for Diabetes Mellitus Type 2 in Educational Hospital North Sumatera University - Soep, Soep; Rinawati, R.R Sri Arini Winarti; Ndama, Metrys (Poltekkes Kemenkes Palu, 2025)
Wound care in a moist environment is superior to a dry environment. Appropriate wound care methods can help accelerate the healing of gangrenous wounds. This study aimed to determine diabetic wound healing using the modern hydrocolloid dressing method. This experimental research design utilized pre-test and post-test techniques to assess the difference in the effect of gangrene wound care with modern hydrocolloid dressings on gangrene wound healing in diabetic patients. The study was conducted at USU Teaching Hospital Medan for 14 days, involving 20 respondents with Type II DM patients experiencing gangrene wounds, obtained through non-probability sampling. Data analysis was performed using the independent t-test. The results showed a significant difference in gangrene wound care with the modern hydrocolloid dressing method (p < 0.05). The modern hydrocolloid dressing method led to faster healing of gangrene wounds. Conclusion: respondents who used the modern hydrocolloid dressing method experienced better wound status development and faster healing. It is expected that hospitals will plan and establish SOPs for wound care in DM patients with gangrene using modern hydrocolloid dressings and reduce the use of conventional methods. These implications highlight the importance of implementing modern methods in wound care protocols for patients with diabetes mellitus with gangrene, mainly to prevent amputation and improve patients' quality of life. Recommendations include the implementation of modern wound care SOPs, training for health workers, patient and family education, further research, and the procurement of modern dressings.